Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
How to solve this derivative?
I tried solving this but I end up with big powers of x combined...
What's the derivative of:
F(x)= x/(x^2 + 2x -3). ??
What's the derivative F' of this function?
3 Answers
- MechEng2030Lv 78 years agoFavorite Answer
F '(x) = -x(2x + 2)/(x^2 + 2x - 3)^2 + 1/(x^2 + 2x - 3)
F '(x) = (-2x^2 - 2x + x^2 + 2x - 3)/(x^2 + 2x - 3)^2
F '(x) = (-x^2 - 3)/(x^2 + 2x - 3)^2
- 8 years ago
Find the derivative of the following via implicit differentiation:
d/dx(F(x)) = d/dx(x/(x^2+2 x-3))
The derivative of F(x) is F'(x):
F'(x) = d/dx(x/(-3+2 x+x^2))
Use the quotient rule, d/dx(u/v) = (v ( du)/( dx)-u ( dv)/( dx))/v^2, where u = x and v = x^2+2 x-3:
F'(x) = ((x^2+2 x-3) d/dx(x)-x d/dx(-3+2 x+x^2))/(x^2+2 x-3)^2
The derivative of x is 1:
F'(x) = (-(x (d/dx(-3+2 x+x^2)))+1 (-3+2 x+x^2))/(-3+2 x+x^2)^2
Simplify the expression:
F'(x) = (-3+2 x+x^2-x (d/dx(-3+2 x+x^2)))/(-3+2 x+x^2)^2
Differentiate the sum term by term and factor out constants:
F'(x) = (-3+2 x+x^2-d/dx(-3)+2 d/dx(x)+d/dx(x^2) x)/(-3+2 x+x^2)^2
The derivative of -3 is zero:
F'(x) = (-3+2 x+x^2-x (2 (d/dx(x))+d/dx(x^2)+0))/(-3+2 x+x^2)^2
Simplify the expression:
F'(x) = (-3+2 x+x^2-x (2 (d/dx(x))+d/dx(x^2)))/(-3+2 x+x^2)^2
The derivative of x is 1:
F'(x) = (-3+2 x+x^2-x (d/dx(x^2)+1 2))/(-3+2 x+x^2)^2
Use the power rule, d/dx(x^n) = n x^(n-1), where n = 2: d/dx(x^2) = 2 x:
F'(x) = (-3+2 x+x^2-x (2+2 x))/(-3+2 x+x^2)^2
Expand the left hand side to find the answer:
F'(x) = (-3+2 x+x^2-x (2+2 x))/(-3+2 x+x^2)^2
Source(s): Wolfram|Alpha - PolygonLv 78 years ago
y = u/v where both u and v are functions of x
dy/dx = [v*(du/dx) - u*(dv/dx)]/v^2
F'(x) = [(x^2 + 2x - 3) - x(2x + 2)]/[(x^2 + 2x + 3)^2]
F'(x) = [-x^2- 3]/[(x^2 + 2x + 3)^2]